Analisis Penerapan Prinsip 5C Dalam Keberhasilan Pembiayaan Mikro Ib di BRI Syariah Kantor Cabang Pembantu (KCP) Sidoarjo Gateaway - Hendro Rumpoko; Wilda al Aluf (Yos Soedarso Economic Journal (YEJ), 2022)
In Bank BRI Syariah, micro iB financing is divided into three, namely micro 25iB, micro 75iB and micro 200iB. iB microfinance is financing provided to customers who own a business and need working capital with a minimum length of business of two years which is generally individual in nature and provides loan facilities, where the borrower/finance applicant is required to provide collateral or guarantees. The purpose of this research activity is to determine the application of 5C principle analysis to the implementation of iB micro-financing by BRI Syariah KCP Sidoarjo Gateway employees and to determine the impact of implementing customer 5C on the success of iB micro-financing at BRI Syariah KCP Sidoarjo Gateway.